Analisis Faktor Risiko Lingkungan Rumah Dan Praktek Penccgahan Yang Berhubungan Dengan Kejadian Tuberkulosis Paru Di Distrik Nabirc Kabupaten Nabire Provinsi Papua Tahun 20I0 - Alfred Denius Lambey (Pusat Riset dan Inovasi Nasional, 2021)
Based on the data ofNabire District Health Office concerning findings of cases in 2009 which are recorded as TB type patients: Positive BTA Pulmonary TB 209, Positive BTA relapsed TB 3, Negative BTA but positive Rontgen about 625 cases, Extra Pulmonary Pediatric patients 72 and 175 with total number for all cases of each type of TB patients about 1083 persons. The aim of this study is to analyse the risk factors of home environment Pulmonary Tuberculosis related Prevention Practices in Nabire Regency. The research design was observasionally retrospective study with case control study design. All of the patients who had been diagnosed as Positive BTA Pulmonary TB through microscopic examination both in the hospitaJ or Community Health Center (Puskesmas) laboratory were taken as the sample of the study, in January - July 2010 periode. Matching separation that based on age and gender, the control group member is each person who more or less has the same characteristic with the case group, live at Nabire district and 15 years of aged, as part of the case group neighbours but does not suffer pulmonary TB. The results indicate a signicantly relationship between occupation density (p = 0,001); OR= 4,376), in room ventilation (p = 0,001; OR = 3,541), in house ventilation (p = 0,017; OR= 2,637), in room lighting intensity (p = 0,017; OR= 2,615), in house lighting intensity (p = 0,002; OR= 3,455), in room hwnidity (p = 0,037; OR = 2,406), in house humudity (p = 0,001 ; OR = 4,376), presence of window in room (p= 0,002; OR= 3,500), in room temperature (p = 0,131; OR= 2,143), in house temperature (p = 0,001; OR= 3,984) with incidence of Pulmonary Tuberculosis. There is no relationship between floor type (p = 0,001; OR = 4,376) and separation room (p = 0,851;OR = 0,869) with the incidence of Pulmonary Tuberculosis. It is suggested to attempt the increment of Pulmonary tuberculosis findings, improvement of house environtment condition with emphasized on sanitation aspect of healthy house at the time of build, and increase clean and healthy behaviours.